AN EXPERIMENTAL STUDY OF AN ATTEMPT IN IMPROVING THE STUDENTS’ WRITING SKILLS - Albert Efendi Pohan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
This study was designed at identifying the effect of Project-Based Learning implementation on the secondary students’ writing skills at the tenth grade of senior high school 21 Batam. The design of this research was running by quasi-experimental research non-equivalent control group design. The research variable consists of a control class as a dependent variable and the experiment class as an independent variable. To meet the purposes of the research, the researcher selected all the tenth grades students to be the participants of this research. Both of the classes first science class and second science class were the samples of this research. The data were collected through the running written test which consists of pre-test and post-test (in which the participants wrote the simple recount text). The analysis of data used a one-sample t-test with a significance level 5%. The statistic process showed that the t-test is bigger than the t-table. Means, the result of this study showed that the Project-Based Learning gave the effect toward the secondary students’ writing skill in simple recount text.